PENERAPAN MODEL ACTIVE LEARNING PERMAINAN CARD SORT UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MATEMATIKA SISWA KELAS IV SDN 05 METRO SELATAN - Muncarno Muncarno (UNIVERSITAS MUHAMMADIYAH METRO, 2015)
This research was motivated by the low activities and student learning outcomes on mathematics. The purpose of this research was to increase the activities and student learning outcomes on mathematics by applying the active learning model of card sort game. The method of this research was classroom action research that consist of planning, implementation, observation, and reflection. The instrument of data collection used was observation sheet and test questions. The technique of analysis data used were qualitative analysis and quantitative analysis. The results of this research showed that aplication of active learning model of card sort game on mathematics learning can increase the activities and student learning outcomes. It can be showed that students learning completeness reached 75%, the average activities of students in the first cycle were 59.80% and 78.39% in the second cycle with the increasing of 18.59%. The average student learning outcomes in the first cycle and the second cycle were 69.52 78.70, with an increase of 9.18.